Pengaruh Pendekatan Konflik Kognitif Terhadap Penguasaan Konsep Fisika Peserta Didik - Martina Nur Larasafitri; Sutrio Sutrio; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2018)
This research aimed at measure the effect of cognitive conflict approach on the mastery of physics concept of students. Cognitive conflict is an approach consisting of preliminary, conflict, and settlement phases. This quasi-experimental research uses non-equivalent group design. The population of this research was all XI IPA students of SMAN 6 Mataram in academic year 2017/2018. The sample was chosen using cluster random sampling, with XI IPA 1 as experiment class and XI IPA 2 as control class. The instrument used for concept mastery refers to students cognitive abilities (C1, C2, C3, C4, C5, C6). Hypothesis test using t pooled varians. The improvement of concept mastery is determined based on the results of the n-gain test. The results of research indicate the influence of cognitive conflict approach on the mastery of physics concept of students. In addition, the experimental class experienced an increased mastery concept higher than control class. This suggests the cognitive conflict approach applied successfully improves the mastery of the physics concepts of students, especially on sub material nature of material elasticity, Hooke law, and the arrangement of springs.